Explicit OR-dispersers with polylogarithmic degree. - Saks, Michael (Journal of the ACM)
An (N, M, T)-OR-disperser is a bipartite multigraph G=(V, W, E) with |V| = N, and |W| = M, having the following expansion property: any subset of V having at least T vertices has a neighbor set of size at least M/2. For any pair of constants &xgr;, &lgr;, 1 ≥ &xgr; > &lgr; ≥ 0, any sufficiently large N, and for any T ≥ 2(logN) M ≤ 2(log N)&lgr;, we give an explicit elementary construction of an (N, M, T)-OR-disperser such that the out-degree of any vertex in V is at most polylogarithmic in N. Using this with known applications of OR-dispersers yields several results. First, our construction implies that the complexity class Strong-RP defined by Sipser, equals RP. Second, for any fixed &eegr; > 0, we give the first polynomial-time simulation of RP algorithms using the output of any ?&eegr;-minimally random? source. For any integral R > 0, such a source accepts a single request for an R-bit string and generates the string according to a distribution that assigns probability at most 2−R&eegr; to any string. It is minimally random in the sense that any weaker source is insufficient to do a black-box polynomial-time simulation of RP algorithms.